Optimización del tratamiento térmico para la inducción al desove de Argopecten purpuratus (Mollusca: Bivalvia) (Revista de Biología Marina y Oceanografía, 2021)
Based on methodologies currently used in commercial hatcheries, four thermic treatments were compared to induce the gametes expulsion of Argopecten purpuratus. The treatments evaluated included: 1) gradual increase in temperature, 2) gradual decrease, 3) 5 °C thermal-shock, 4) 10 °C thermal-shock and 5) control at constant temperature 16 °C. After induction, the number of fertilized oocytes in each treatment was estimated. The results show that a gradual increase in temperature between 16 and 26 °C causes a significantly higher proportion of fertilized oocytes compared to other treatments.